Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT X Di Sidoarjo - Finda Nur Afifah; Aisyah Darti Megasari (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine the effect of compensation and work motivation on employee performance at PT X using a quantitative approach, The numbernof samples used in this research was 100 PT X employees. The data collection technique used was a questionnaire technique. The data analysis techniques used are multiple linear regression, classical assumption test, t test, f test and coefficient of determination. Based on analysis using the t test, it can be seen that the independent variables compensation (X1) and work motivation (X2), partially have a positive anda significant effect on the dependent variable (Y) is employee performance. Then the result of the analysis using f testcan be seen that the independent variables compensation and work motivation together have a significant effect on the dependent variable, namely employee performance (Y). The result on the analysis using the coefficient of determination show that 61.2% of employee performance is influenced by compensation dan work motivation, while the remaining 38,8% in influenced by other variables not included in this study.